2012
DOI: 10.15376/biores.7.4.4760-4775
|View full text |Cite
|
Sign up to set email alerts
|

Plasticizing Effect of Choline Chloride/Urea Eutectic-Based Ionic Liquid on Physicochemical Properties of Agarose Films

Abstract: Agarose films were formed with the addition of 30 to 70 wt% choline chloride/urea eutectic-based ionic liquid (ChCl/Urea). The ChCl/Urea was prepared through complexation at a 1:2 mole ratio. The films were prepared by dissolving ChCl/Urea in distilled water followed by dispersion of the agarose at 95 °C. The solution was gelled at room temperature, and the formed gel was dried in an oven overnight at 70 °C. Mechanical testing indicated that the agarose film containing 60 wt% ChCl/Urea had higher tensile exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…The stretching vibrations of alcohol in both 1, 4-butanediol and choline chloride, ChCl shifted to lower frequencies from 3340 cm -1 in ChCl (Park et al 2013) to 3294 cm -1 in 1,4-butanediol DES, which was prepared by mixing two components. It is known that the existence of the main hydrogen bonding in DES was due to the bonding between Cl -ion in ChCl and hydrogen donor molecule (Shamsuri & Daik 2012). Nevertheless, the shift to lower frequencies of hydroxyl stretching vibration could be attributed to the potential hydrogen bond formation through hydroxyl group in ChCl.…”
Section: Structural Elucidation Of Deep Eutectic Solvent (Des) and Inmentioning
confidence: 95%
“…The stretching vibrations of alcohol in both 1, 4-butanediol and choline chloride, ChCl shifted to lower frequencies from 3340 cm -1 in ChCl (Park et al 2013) to 3294 cm -1 in 1,4-butanediol DES, which was prepared by mixing two components. It is known that the existence of the main hydrogen bonding in DES was due to the bonding between Cl -ion in ChCl and hydrogen donor molecule (Shamsuri & Daik 2012). Nevertheless, the shift to lower frequencies of hydroxyl stretching vibration could be attributed to the potential hydrogen bond formation through hydroxyl group in ChCl.…”
Section: Structural Elucidation Of Deep Eutectic Solvent (Des) and Inmentioning
confidence: 95%
“…The broad bands with strong intensity in the region of 3416 to 3400 cm -1 were assigned to the O-H bond stretching vibration of alcohol groups and absorbed water. The peak at 1638 cm -1 in the FTIR of METMA was corresponded to C=C bond stretching of alkene group, whereas the band with medium intensity around 1636 cm -1 was attributed tightly absorbed water by MCC-BiB [10]. The absence of C=C peak in the FTIR of CiB-g-METMA indicated that the METMA monomer had undergone polymerization reaction.…”
Section: Figure 2 (A)mentioning
confidence: 96%
“…Besides composite preparation, it is also possible to confine ILs as gel matrices by cooling biopolymer-IL solutions at ambient temperatures to form "ionogels" which are shown to be smart polymeric conducting materials that combine the chemical versatility of an ionic liquid with the morphological versatility of a biopolymer. 30,31,[38][39][40][41][42][43][44][45][46][47] Such ionogels have been found to be suitable for an array of electrochemical applications. 38,46 Therefore, in addition to the preparation of AG-CH composites, we have attempted to prepare AG-CH-IL composite ionogels using a high solvating ability IL, 3 ) with a purity of 98% mass fraction was purchased from SD FINE CHEM, Mumbai.…”
Section: Introductionmentioning
confidence: 99%